Comprehensive Analysis of Cytochrome P450 Monooxygenases Reveals Insight Into Their Role in Partial Resistance Against Phytophthora sojae in Soybean - Khatri, Praveen; Wally, Owen; Rajcan, Istvan; Dhaubhadel, Sangeeta (Frontiers in Plant Science, 2022)
Cytochrome P450 monooxygenases (P450) participate in the catalytic conversion of biological compounds in a plethora of metabolic pathways such as the biosynthesis of alkaloids, terpenoids, phenylpropanoids and hormones in plants. Plants utilize these metabolites for growth and defence against biotic and abiotic stress. In this study, we identified 346 P450 (GmP450) enzymes encoded by 317 genes in soybean where 26 GmP450 genes produced splice variants. The genome-wide comparison of both A-type and non-A-type GmP450s for their motifs composition, gene structure, tissue-specific expression and their chromosomal distribution were determined. Even though conserved P450 signature motifs were found in all GmP450 families, larger variation within a specific motif was observed in the non-A-type GmP450s as compared to the A-type. Here, we report that the length of variable region between two conserved motifs is exact in the members of the same family in majority of the A-type GmP450. Analyses of the transcriptomic datasets from soybean-Phytophthora sojae interaction studies, QTL associated with P. sojae resistance and co- expression analysis identified some GmP450s that may be, in part, play an important role in partial resistance against P. sojae. The findings of our CYPome study provides novel insights into the functions of GmP450s and their involvements in metabolic pathways in soybean. Further experiments will elucidate their roles in general and legume-specific function.